2001
DOI: 10.1099/00221287-147-8-2169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcription of the bph locus of Burkholderia sp. strain LB400 and evidence that the ORF0 gene product acts as a regulator of the bphA1 promoter

Abstract: Although gene clusters for the degradation of biphenyls and polychlorobiphenyls have been extensively characterized, comparatively little is known about the regulation of their expression. In the present work, different aspects of transcription of the bph locus of the potent polychlorobiphenyl degrader Burkholderia sp. strain LB400 were investigated. An RNA blot analysis of the entire gene cluster revealed that the transcription of all genes encoding biphenyl catabolic enzymes responded similarly to the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Moreover, the studies confirmed the bph pathway (Fig. 1B) was induced during growth on biphenyl, consistent with one published report, but not another (2,24). Finally, it was revealed that C 1 metabolic pathways were induced upon transition towards stationary phase.…”
supporting
confidence: 78%
“…Moreover, the studies confirmed the bph pathway (Fig. 1B) was induced during growth on biphenyl, consistent with one published report, but not another (2,24). Finally, it was revealed that C 1 metabolic pathways were induced upon transition towards stationary phase.…”
supporting
confidence: 78%
“…These authors also suggested that there are two constitutive 70 -dependent promoters upstream of bphA1. However, mutational studies and Northern blot analyses performed by Beltrametti et al (2), who proposed that ORF0 is a positive regulator of bphA1A2, and our observation of increased expression ratios of the bph genes with increased ORF0 expression indicate that there is a positive regulatory function of ORF0 induced by biphenyl. The similarity in expression patterns among ORF0, bphJ, and bphI and possibly bphD suggests that ORF0 is an inducer of bphJ, bphI, and bphD.…”
Section: Discussionmentioning
confidence: 78%
“…Burkholderia xenovorans strain LB400 (17) is one of the most-studied and effective aerobic PCB degraders known and is able to cometabolically degrade up to hexachlorinated biphenyls (3,8,12,18,22,(31)(32)(33). Although the operon organization for the upper biphenyl degradation pathway (the upper Bph pathway) has been extensively documented, there are contradictory reports on its regulation, suggesting that there is constitutive (5,25) or biphenyl-induced expression (2,12,27). The enzymatic reactions of the upper Bph pathway result in formation of benzoate and pentadiene or their chlorinated derivatives.…”
mentioning
confidence: 99%
“…The transcription of the bph locus of Burkholderia sp. strain LB400, whose bph genes are very similar to those of KF707, was investigated (9). In this system, the ORF0 protein (corresponding to KF707 BphR1) mediates the activation of the bphA1 promoter.…”
Section: Versatile Regulation Of Bph Genesmentioning
confidence: 99%